Completion rates and injuries in alpine races during the 1994 Olympic Winter Games - Ekeland, A.; Dimmen, S.; Lystad, H.; Aune, A. K. (Scandinavian Journal of Medicine & Science in Sports, 1996)
The starting lists for the alpine disciplines during the 1994 Olympic Winter Games in Lillehammer totalled 555 racers, but only 354 of them (64%) completed the different races. The race completion rate was 43% in the slalom, 51% in the giant slalom, 75% in the super giant slalom and 91% in the downhill. In combined downhill/slalom the race completion rate was 60%, but 96% in the downhill and 68% in the slalom part of the combination, respectively. Only three injuries were recorded, all in females. Including the training competitions a total of 1541 runs through the different alpine courses was recorded during the games. This means an injury rate of 1.9 injuries per 1000 runs. For downhill the injury rate was only 1.1 per 1000 runs. If the injury rate is related to the number of skiers who did not finish the race because of falls or skiing errors, the rate was 21.1 injuries per 1000 falls (skiing errors) for all alpine races. In conclusion, the race completion rate was twice as high in downhill as in slalom, and the injury rate was low. Scand J Med Sci Sports 1996 Oct;6(5):287-90